Art practice, process, and new urbanism in Dublin: Art Tunnel Smithfield and social practice placemaking in the Irish capital - Courage, Cara (Irish Journal of Arts Management and Cultural Policy, 2017)
This paper presents research with Art Tunnel Smithfield (ATS), Dublin, positioning it in Dublin-wide placemaking practices, and situating it within the city’s tracts of vacant land and Dublin’s bespoke new urbanism. It focuses on the project as a form of social arts practice, giving examples of arts activities and agencies in the space, and locating the work within placemaking typology as ‘social practice placemaking’ (SPPM). SPPM is conceptualised as an extension of participatory public/new genre public art (Lacy, 2008) to a ‘new situationism’ (Doherty, 2004). This perspective views the co-production of art as constructive of new spatial configurations and emergent relations between users and space. Locating this work in the socio-politics of urban life, SPPM has to be understood as an art form that dematerializes the built object and is concerned with creative and social processes and outcomes.